Inter and intralayer basalt hybrid effects on the static and vibrational behaviors of Brazilian curauá/basalt hybrid composite. (2020) - Premkumar, T.; Siva, I.; Amico, Sandro C
Abstract: In this study, effect of the keeping basalt fiber hybrid as interlayer and intralayer to the curauá fiber polyester composites to alter the vibrational properties is experimented. Hybrid composites are fabricated by keeping relative hybrid percent as 50 for both the inter and intra-layer specimens. Experiments are conducted as per ASTM recommendation to measure the tensile and flexural properties. Modal analysis was done with impact hammer excitation technique; natural frequency and damping are reported. Results are compared with the pure curauá/polyester (100:0) and pure basalt/polyester composites (0:100). Experiment shows that, the vibrational properties of the hybrid composite exhibit superior nature when compared to the neat fiber composites. In the meantime, among the layer sequences, no such significant difference is noted between the inter and intra layer composites. The results attribute the behavioral stability of the curauá and basalt hybridization. Fractography is done with the electron microscopy and reveals that, the interlayer composite has more fiber entanglements than the intralayer composites.